Psychometric Analysis of the EQ-i-M20 in Chilean University Students - Guerra Díaz, Felipe Esteban (2025)
The Brief Emotional Intelligence Inventory (EQ-i-M20) was designed to assess emotional intelligence in individuals. Its application in educational contexts allows the identification of areas for intervention and development. This study aimed to evaluate its psychometric properties. It used an instrumental design and 500 Chilean university students participated. The factor structure of the instrument was examined through confirmatory factor analysis and factorial invariance tests were performed. The structural analysis revealed that the five-factor model of the EQ-i-M20 showed favorable fit indicators (X²=267.278, gl=160, p<0.001; CFI=0.986; TLI=0.984; RMSEA=0.033; SRMR=0.042). In addition, the factorial invariance analysis confirmed the equivalence of the model between men and women, suggesting that it equitably measures emotional intelligence in both genders. These results are relevant as they provide background information regarding an appropriate tool for assessing emotional intelligence in university students.